Adjustment of the crystal structure of titanium dioxide during the deposition of ammonium hexafluorotitanate; International Symposium on Inorganic Fluorides: Chemistry and Technology - Dubov A. G. Aleksandr Georgievich (2014, 2014)
Title screen.